Preschool age children in the educational process, the importance - Qulliyeva Sevara Vahob qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
this article on "Importance of preschool children in the educational process" rolan is an important development in preschool children. At preschool ages, children study not only knowledge and skills but also form the main foundation of personal and social development. The importance of play and activities in the educational process, the teacher rolan, as well as the cooperation between the family and the educational institute for speed is discussed in the child's your support emotional and cognitive development. Also, the use of individual approaches is analyzed by teachers and educators in the development of the modern metho their personal abilities. The impact of this article on the importance of preschool education, psychology and physical development, social skills and social the format of the significance of the educational process is covered extensively. Prompt, in developing the activity of children's identity the importance of training self awareness is an individual and independent thinking is emphasized. The article strives to cover not only preschool children, but also the contribution to society.